New light on China's rural elites - Bjorn Gustafsson; Ding Sai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper analyses political elites, economic elites, hybrid elite households and non-elite households in rural China using household data for 1995 and 2002. We seek to understand the determinants of belonging to each of the three elite categories. We find that education and military experience positively affect the probability of being a political elite. The probability of becoming an economic elite is linked to the age of the head of household and to the income level of the county, indicating that opportunities to become an economic elite have increased over time, but in a spatially uneven way.We also investigate disparities in household per capita income as well as in household per capita wealth. Asia Market Transition Theory, we find that the relationship between education and the household's economic status became stronger from 1995 to 2002. This theory also predicts that payoffs from belonging to the political elite decrease during transition towards market economy. Our results show that in the richest counties in 2002, the economic gain from being a political elite household was higher than elsewhere and higher than in high-income counties observed in 1995. We also found that although elite households on average have a better economic situation than non-elite households, income inequality and household wealth inequality in rural China would decrease only marginally if such disparities were to vanish. In contrast the spatial dimension is much more important for income inequality and for wealth inequality in rural China.
Keywords: D31; P32; P36; 330; China; elites; cadre; entrepreneur